Strategies for Community Empowerment through Social Entrepreneurship to Support Sustainable Economic Development - Amruddin; Yani, Ahmad; Ausat, Abu Muna Almaududi (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
This study aims to examine strategies for community empowerment through social entrepreneurship in supporting sustainable economic development. Using a literature review approach and descriptive analysis, the research explores relevant literature published between 2017 and 2024. Data were collected from 30 articles on Google Scholar, which were then filtered to 18 articles meeting quality and relevance criteria. The findings indicate that social entrepreneurship positively impacts community empowerment by creating sustainable economic and social opportunities. Case studies analyzed, such as Nglanggeran Tourism Village, Sababay Winery, and Difalink, highlight that cross-sector collaboration, technology adoption, and data-driven management are key success factors. However, challenges such as limited access to capital, infrastructure, and technology hinder the implementation of social entrepreneurship. Therefore, collaboration between government, private sector, and communities is essential to overcome these barriers and enhance the effectiveness of community empowerment through social entrepreneurship.